2013
DOI: 10.1016/j.ijggc.2013.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating time-lapse borehole gravity for CO2 plume detection at SECARB Cranfield

Abstract: a b s t r a c tMonitoring of CO 2 storage processes provides a renewed challenge of adapting oil and gas monitoring technology to provide measurements required of operator, regulatory authorities and the public. These requirements include providing measurements that will support an understanding of safe containment of the CO 2 plume, and inform evidence that injected CO 2 remains in the storage complex for the purposes of green house gas accounting, cost effectively. These roles for monitoring demand a re-eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Gaussian noise with a 10 μgal standard deviation is added to gravity changes simulated in the borehole. Borehole time‐lapse measurements are expected to be noisier that surface measurements because of a combination of instrumental and set‐up errors due to depth positioning of the borehole gravimeter …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaussian noise with a 10 μgal standard deviation is added to gravity changes simulated in the borehole. Borehole time‐lapse measurements are expected to be noisier that surface measurements because of a combination of instrumental and set‐up errors due to depth positioning of the borehole gravimeter …”
Section: Methodsmentioning
confidence: 99%
“…Its amplitude is comparable to that of the errors associated to time‐lapse gravity surveys, typically 5 μgals . To overcome the issue of distance between the measurements and the plume, borehole time‐lapse measurements have been suggested and numerically studied, and the first results from actual measurements are promising and hint at the detection of density changes associated to CO 2 storage at SECARB Cranfield site …”
Section: Introductionmentioning
confidence: 97%
“…Natural tracers (isotopically distinctive CO 2 ) and dissolved methane in reservoir brine and emplaced pulses of SF 6 , PFT, and noble gas tracers provided data on fluid flow not available from imaging (Lu et al, 2012a). A well-bore gravity tool was deployed and was able to detect changes due to substitution of CO 2 in relatively thin intervals (Dodds et al, 2013). In addition, a baseline 3-D seismic survey was conducted over the field with a repeat survey after injection of the first 1 million metric tons.…”
Section: Secarb Cranfield Early Testmentioning
confidence: 99%
“…Well-based gravity was tested at Cranfield and was successful in obtaining signal from injected CO 2 (Dodds et al, 2013) and is in testing at several EOR fields.…”
Section: Gravimetrymentioning
confidence: 99%
“…Time-lapse gravimetry has been used extensively in oil and gas production monitoring (e.g., Alnes et al, 2008;Brady et al, 2008;Eiken et al, 2008;Ferguson et al, 2008;Alnes et al, 2011;Dodds et al, 2013) and in groundwater and aquifer studies (e.g., Cogbill et al, 2006;Davis et al, 2008;Gehman et al, 2009). A more comprehensive review can be found in Krahenbuhl and Li (2012).…”
Section: Time-lapse Gravity and Gravity Gradiometrymentioning
confidence: 99%